Risk factors and complications in pregnancies associated with placenta previa among admitted cases in FMCH - Ghosh, Abanti; Rani Ghosh, Suchita; Das, Mita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Placenta previa is a leading cause of antepartum haemorrhage. Placenta previa present a significant clinical problem and patients are at risk for significant haemorrhage, needing blood transfusion. The risks are increased in women with previous placenta previa, endometrial damage caused by DE and C, caesarean delivery, myomectomy, multiparity, alcohol cocaine use during pregnancy, smoking during pregnancy. Methods: Admitted patients were selected with convenience sampling type of non-probability sampling type of non-probability sampling technique. The primary end point was to determine the risk factors of placenta previa and its complications. The secondary end point was to determine maternal morbidity and mortality of placenta previa. Results: Incidence of placenta previa was 2.03% out of 2459 patients, 70% were associated with risk factors. Among them 42% had history of caesarean section, 14% had history of abortion, 10% had history of manual removal, 48% patients were more than 25% years old, 36% were more than 30 years. Placenta previa occurred in gravida 3rd or more. Forty two percent patients belonged to lower socioeconomics group. Only 12% patients had regular antenatal checkup. Malpresentations were present in 24% cases. In this study 50% patients were associated with central placenta previa. Eighty percent patients were in shock, only 2% patients were asymptomatic. Regarding management 76.34% patients were managed actively, 12% patients had expectant management. Only 2% patients delivered vaginally, 82% patients delivered by caesarean section. Maternal mortality rate was 02%. Regarding fetal outcome, 76% babies were alive and there were 20% perinatal deaths. Conclusions: Although etiology of placenta previa largely remain obscure and speculative. There is a strong association between advanced maternal age, multiparity, history of caesarean section and abortion with subsequent development of placenta previa. Women aged >30 years, grand multipara, previa and must be monitored carefully. Hence the study advocates proper antenatal care early referral to hospital and prompt management of patients after proper selection can reduce maternal morbidity and mortality.